UJI MODEL FISIK RAYAPAN GELOMBANG PADA REVETMEN BUIS BETON - Juventus Welly Radianta Ginting; Eduardo Meyrianso Simanjuntak; Ida Ayu Irawati Diah Ratna Putra (JURNAL TEKNIK HIDRAULIK, 2021)
Buis Beton (Precast concrete pipe) revetment is a common coastal structure to protect the shoreline from erosion. However, it is common that this type of structure face high wave run up. A continuous wave run up on the slope of the structure may reduce the life service of Buis Beton revetment. The objective of this research is to create scientific based guidance to design an efficient Buis Beton revetment against wave run up. A physical modelling test is conducted to understand the relationship between wave run up and Buis Beton revetment. The test scenario is based on the slope of the structure (θ), structure height (L), buis beton diameter (φ), incoming wave height (Hi) and wave period (T). The physical modelling is conducted in 2D wave flume with laboratory scale of 1:10 with regular wave simulation. Wave run up is observed using a video camera which is later processed digitally to acquire the wave run up data. This research shows that the relative wave run up has a reciprocal functional relationship with the Iribarren Number parameter. In general, wave run up height on Buis Beton revetment is less than or equal to 2.64 the wave height, Hm0.Keywords: Revetment, buis beton, wave run-up, physical modelling